Improving the Business Climate in Russia - Radziwill, Artur (OECD Economics Department Working Papers, 2015)
Economic growth is below what would be needed to resume rapid convergence to average OECD living standards. On-going efforts to improve the business climate are laudable, but need to be widened and strengthened. Much progress has been achieved in reducing red tape, but it is only recently that the authorities have visibly become more energetic in fighting corruption. Adverse interactions between politics, business and law enforcement generate obstacles for the rule of law and remain a major risk for potential investors. High entry barriers lead to weak competition. Reducing the role of the state in the economy and WTO membership should be viewed as opportunities to strengthen competition, and hence provide incentives for productivity improvements, which are urgently required to ensure stronger growth in Russia because of a shrinking labour force. This Working Paper relates to the 2013 OECD Economic Survey of the Russian Federation (www.oecd.org/eco/surveys/economic-survey-russian-federation.htm)